2019
DOI: 10.1101/528372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ketamine Affects Prediction Errors about Statistical Regularities: A Computational Single-Trial Analysis of the Mismatch Negativity

Abstract: The auditory mismatch negativity (MMN) is significantly reduced in schizophrenia. Notably, a similar MMN reduction can be achieved with NMDA receptor (NMDAR) antagonists. Both phenomena have been interpreted as reflecting an impairment of predictive coding or, more generally, the "Bayesian brain" notion that the brain continuously updates a hierarchical model to infer the causes of its sensory inputs. Specifically, predictive coding views perceptual inference as an NMDAR-dependent process of minimizing hierarc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 77 publications
(94 reference statements)
3
42
0
Order By: Relevance
“…Trial-wise estimates of uncertainty -or its inverse, precision -serve to scale the impact of prediction errors (PEs) on the belief updates. Consistent with previous reports (Stefanics et al, 2018;Weber et al, 2019), we found that precision-weighted PEs (pwPEs) on two hierarchical levels can explain trial-wise modulation of observed ERP responses in control participants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Trial-wise estimates of uncertainty -or its inverse, precision -serve to scale the impact of prediction errors (PEs) on the belief updates. Consistent with previous reports (Stefanics et al, 2018;Weber et al, 2019), we found that precision-weighted PEs (pwPEs) on two hierarchical levels can explain trial-wise modulation of observed ERP responses in control participants.…”
Section: Discussionsupporting
confidence: 92%
“…Lower level pwPEs about the reward outcomes, updating beliefs about reward tendency and higher-level pwPEs about reward tendencies, updating volatility estimates, were primarily represented across frontocentral regions, with an earlier latency for ε3 (387 ms) than ε2 (453 ms). These results align with previous studies combining EEG analyses with the HGF, which revealed that multiple, hierarchically-related pwPEs are computed while learning in volatile environments; and these are represented across different brain regions specific to the task demands (Diaconescu et al, 2017a;Stefanics et al, 2018;Weber et al, 2019).…”
Section: Hierarchically-related Prediction Errors Modulate Trial-by-tsupporting
confidence: 90%
See 3 more Smart Citations